Genetic and virulence characteristics of hybrid Shiga toxin-producing and atypical enteropathogenic Escherichia coli strains isolated in South Korea - Lee, Woojung; Ha, Jina; Choi, Jaehyun; Jung, Yewon; Kim, Eiseul; An, Eun Sook; Kim, Seung Hwan; Shin, Hakdong; Ryu, Sangryeol; Kim, Soon Han; Kim, Hae-Yeong (Frontiers in Microbiology, 2024)
Introduction The predominant hybrid pathogenic E. coli, enterohemorrhagic E. coli (EHEC), combines characteristics of Shiga toxin-producing E. coli (STEC) and enteropathogenic E. coli (EPEC), contributing to global outbreaks with severe symptoms including fatal consequences. Since EHEC infection was designated as a notifiable disease in 2000 in South Korea, around 2000 cases have been reported, averaging approximately 90 cases annually. Aim In this work, genome-based characteristic analysis and cell-based assay of hybrid STEC/aEPEC strains isolated from livestock feces, animal source foods, and water in South Korea was performed. Methods To identify the virulence and antimicrobial resistance genes, determining the phylogenetic position of hybrid STEC/aEPEC strains isolated in South Korea, a combination of real-time PCR and whole-genome sequencing (WGS) was used. Additionally, to assess the virulence of the hybrid strains and compare them with genomic characterization, we performed a cell cytotoxicity and invasion assays. Results The hybrid STEC/aEPEC strains harbored stx and eae genes, encoding Shiga toxins and E. coli attachment/effacement related protein of STEC and EPEC, respectively. Furthermore, all hybrid strains harbored plasmid-carried enterohemolysin(ehxCABD), a key virulence factor in prevalent pathogenic E. coli infections, such as diarrheal disease and hemolytic-uremic syndrome (HUS). Genome-wide phylogenetic analysis revealed a close association between all hybrid strains and specific EPEC strains, suggesting the potential acquisition of Stx phages during STEC/aEPEC hybrid formation. Some hybrid strains showed cytotoxic activity against HeLa cells and invasive properties against epithelial cells. Notably, all STEC/aEPEC hybrids with sequence type (ST) 1,034 (n = 11) exhibited higher invasiveness than those with E2348/69. This highlights the importance of investigating potential correlations between STs and virulence characteristics of E. coli hybrid strains. Conclusion Through genome-based characterization, we confirmed that the hybrid STEC/aEPEC strains are likely EPEC strains that have acquired STEC virulence genes via phage. Furthermore, our results emphasize the potential increased danger to humans posed by hybrid STEC/aEPEC strains isolated in South Korea, containing both stx and eaeA, compared to STEC or EPEC alone.